Data sharing in transboundary waters: current extent, future potential and practical recommendations - International Water Management Institute (International Water Management Institute, 2021)
Data exchange in transboundary waters is fundamental to advance cooperation in water management. Nonetheless, the degree to which data are actually shared is falling short of basin-level and international targets. A global assessment revealed that a reasonable proportion of river basins exchange some data, but the breadth of such exchange is often limited and not regular. More in-depth examination of African basins nonetheless suggests that a real need for, and use of, water data appears to motivate exchange. Indeed, evidence suggests that data exchange needs which are more directly felt enhance exchange, e.g., the direct need to minimize flood impacts or manage transboundary infrastructure. As such, data sharing is much more likely to be considered as being successful if it responds to a palpable need and serves practical uses. Also, in developing data exchange programs, it may be prudent to adopt a focused and sequential approach to data exchange that starts with a short-list of most needed parameters.